Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0202899
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of cardio-metabolic diseases by population group, gender and adiposity in South Africa

Abstract: AimsTo describe the distribution and examine the associations of diabetes, hypertension and hypercholesterolaemia across and within population groups, gender and body mass index (BMI) categories.MethodsThis national cross-sectional study was conducted in 2013 among ≥18-year-old black African, coloured, white and Indian adults self-selected for screening. Data collection included self-reported behavioural risk factors and clinical measurements comprising blood pressure, anthropometry and point-of-care random bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Some previous studies in SSA populations report stronger associations between BMI and lipids in men than women [8,11,14], whereas we observed similar associations in both sexes in this contemporary Malawian study. Our results of similar or weaker associations in Malawian than UK participants corroborate previous findings of weaker age-adjusted associations of WC with TC and TG in urban Cameroonian women and men than their French counterparts, observed approximately 25 years ago [14].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Some previous studies in SSA populations report stronger associations between BMI and lipids in men than women [8,11,14], whereas we observed similar associations in both sexes in this contemporary Malawian study. Our results of similar or weaker associations in Malawian than UK participants corroborate previous findings of weaker age-adjusted associations of WC with TC and TG in urban Cameroonian women and men than their French counterparts, observed approximately 25 years ago [14].…”
Section: Discussioncontrasting
confidence: 57%
“…Evidence from HIC, from populations of white European origin, shows that higher BMI and measures of central adiposity, such as WHR and WC, are associated with adverse lipid profiles, including higher total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG), which are key modifiable risk factors for coronary heart disease (CHD) [4][5][6]. The body of evidence on this relationship in SSA countries is growing and also showing associations between higher generalised and central adiposity with adverse lipid profile in both men and women [7][8][9][10][11] and adults from urban and rural area [9]. However, very few studies have made direct comparisons between SSA and HIC populations, which have a much more advanced stage of economic development.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of multiple cardiometabolic conditions in people of Indian descent was more than twice that of the black African and mixed-race ethnic groups. Several studies in SA have confirmed a high risk for cardiometabolic diseases, particularly diabetes, in South Africans of Indian descent [ 9 , 30 , 34 ]. Indian Asians have been shown to have a higher risk than White Caucasians for the development of cardiometabolic diseases for the same unit of increase in BMI [ 35 , 36 ] and they may also have genetic markers that increase their susceptibility to diabetes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid and sustained increases in adiposity are likely to be contributory to future cardiometabolic disease risk in women regardless of HIV status. (38)(39)(40) Those living with HIV may be at higher risk of such outcomes, (41,42) though the precise mechanisms are unknown. There is some evidence suggesting that South Africans with HIV receive enhanced levels of care for their obesity-related conditions compared with those without HIV.…”
Section: Discussionmentioning
confidence: 99%